Hepatitis B and C virus infection among Brazilian Amazon riparians - OLIVEIRA, Claudia Suellen Ferro de (2014)
INTRODUCTION: Viral hepatitis is a major public health concern in Brazil. There are few past studies on this issue, especially among riparian communities. This study aims at determining the seroprevalence of viral hepatitis B and C in the riparian community of Pacuí Island, within the Cametá municipality of Pará State, Brazil. Moreover, this study aims to investigate the principal risk factors that this community is exposed to. METHODS: The current study has accessed blood samples from 181 volunteers who have answered an epidemiological questionnaire. Analyses on serological markers have been tested with commercial ELISA kits for detecting HBsAg, total anti-HBc, anti-HBs, and anti-HCV. Within seroreactive patients for HCV, RT-PCR and line probe assay have been performed to identify the viral genotype. RESULTS: In the serological marker analysis for hepatitis B, no reactivity for HBsAg, rate of 1.1% for total anti-HBc, and rate of 19.3% for anti-HBs have been observed. On hepatitis C, 8.8% seroprevalence has been found, in which 62.5% have gotten viral RNA. Among the risk factors studied, the following have been highlighted: non-use of condoms, sharing of cutting instruments, use of illicit drugs, and reports of family disease with HBV or HCV. CONCLUSIONS: The vaccination coverage against HBV is low, and the high prevalence of HCV within this community has been observed.